OTA Multiplier Converts to Two-Quadrant Divider - Malvar, Henrique S. (Electronics, 1981)
An inexpensive two-quadrant analog voltage divide can be built using an operational transconductance amplifier. The design can be useful in analog tunable and tracking filters and special-purpose modulators and demodulators.